The impact of compensation on the threeorganizationnal commitment for Knowledge workers - Yosr TRABELSI (Revue de Gestion des Ressources Humaines, 2009)
The advent of the knowledge society has fostered a new category of workers with high intellectual capital, commonly known as Knowledge workers. These atypical, volatile workers, perfectly aware of their market value, adopt a strategy of “Marketisation”, thereby limiting their organizational commitment. Do the impact of compensation constitute a determinant of knowledge workers’ organizational commitment? The contribution of this article is to clarify the possible remuneration strategies. An exploratory survey conducted with 160 computer programmers in the Tunisian banking sector reveals the importance of different merit rewards modes and the impact of career prospects and incentive practices. Theses three variables forge and positively influence the three-dimensional (emotional, normative and calculated) commitment of knowledge workers to an employer.